2018
DOI: 10.1111/jphp.13040
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizin, an HMGB1 inhibitor, exhibits neuroprotective effects in rats after lithium-pilocarpine-induced status epilepticus

Abstract: Objectives It has been proven that extracellular HMGB1 is involved in progression of neurologic disorders, such as stroke, traumatic brain injury, meningitis and epilepsy. Glycyrrhizin (GL) is a direct inhibitor of HMGB1, and blocks HMGB1 release into the extracellular. We aim in this study to investigate the neuroprotective effects of GL in a rat model after lithium‐pilocarpine‐induced status epilepticus (SE). Methods Adult male SD rats were divided into three groups: Sham group, SE‐group and (SE + GL)‐treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…Recently, GL attenuated neuronal damage and altered disease progression post‐SE by inhibiting HMGB1 activity and its translocation, and protected BBB integrity in an experimental SE model induced by lithium‐pilocarpine (Li et al . ).…”
Section: Hmgb1‐targeting Therapeutic Agents In Epilepsy: An Updatementioning
confidence: 97%
See 1 more Smart Citation
“…Recently, GL attenuated neuronal damage and altered disease progression post‐SE by inhibiting HMGB1 activity and its translocation, and protected BBB integrity in an experimental SE model induced by lithium‐pilocarpine (Li et al . ).…”
Section: Hmgb1‐targeting Therapeutic Agents In Epilepsy: An Updatementioning
confidence: 97%
“…In addition, GL protects rat hippocampus and olfactory bulb from oxidative and inflammatory damage induced by pilocarpine via inhibiting IL-1b and TNF-a in an experimental model of SE, although no antiepileptic properties were reported in this study (Gonz alez-Reyes et al 2016). Recently, GL attenuated neuronal damage and altered disease progression post-SE by inhibiting HMGB1 activity and its translocation, and protected BBB integrity in an experimental SE model induced by lithium-pilocarpine (Li et al 2018).…”
Section: Hmgb1 Inhibitorsmentioning
confidence: 99%
“…Glycyrrhizin is a small-molecule inhibitor of extracellular HMGB1 cytokine activity [103] with the potential to penetrate BBB [104]. The neuroprotective effect of glycyrrhizin has been demonstrated in an array of neurological disorders, including epilepsy [105], TBI [106], and PD [107]. Although the therapeutic effect of glycyrrhizin has not been demonstrated in AD mice with developed Aβ pathology, its effects have been extensively evaluated against several AD-like pathologies such as LPS-induced neuroinflammation and cognitive deficits, as well as in surgery-induced cognitive decline.…”
Section: Effects Of Hmgb1 Neutralization In Admentioning
confidence: 99%
“…Glycyrrhizin, which is an extract of licorice root, is a triterpenoid saponin glycoside used as a natural sweetener and it has been described with potential immunomodulating, anti-inflammatory, hepato-and neuro-protective, and antineoplastic activities [23][24][25][26]. Previous studies have shown that glycyrrhizin suppresses HMGB1 expressions and mitogenic activities, and impedes its DNA-binding function.…”
Section: Introductionmentioning
confidence: 99%